The reality and challenger of the Islamic sukuk industry The Malaysian experience "a model" - haouat, aboubakr; dhouifi, hamza (Journal of Research in Finance and Accounting, 2021)
The study has been aimed at exposing the reality of Islamic sukuk production and the challenges it faced through analyzing the amount of the production worldwide in general, and in Malaysia in particular because this latter is among the leading countries in this field. The study has resulted at the fact that Islamic sukuk production has always continued attracting increasing numbers of new Islamic sukuk producers, and this reflects the positive consequences that have been realized worldwide and providing suitable finance for various projects moreover, it shows that the success of the Malaysian example in Islamic sukuk production is thanks to several factors like legal framework and organizational and observational environment. Yet, there are some obstacles preventing its development like religious factors.